PENGGUNAAN LOGGER PRO UNTUK ANALISIS GERAK HARMONIK SEDERHANA PADA SISTEM PEGAS MASSA - DANDAN S LUHUR ARASWATI (Faktor Exacta, 2016)
There have been research which aims to know a graph of simple harmonic motion by using video based laboratory. Data collection is using video recording oscillation the mass spring system, then the video is analyzed with Logger Pro. Results of the analysis were presented with data and graph. Based on the analysis and fitting the data using Logger Pro value obtained as A = 0.2397 m, ? = 4.888 rad/s, k = 7.168 N/m. The value of kinetic energy, potential energy, and mechanical energy can be determined the magnitude and presented in graph by using Ms. Excel. Analysis of the shape graph is approaching theory. Thus the results of this research can be used as a medium of learning to describe and prove the graph of simple harmonic motion. Key words: simple harmonic motion, mass spring system, Logger Pro